Moth flame optimization based design of linear and circular antenna array for side lobe reduction. (28th September 2018) - Das, Avishek; Mandal, D.; Ghoshal, S.P.; Kar, R.
Abstract: This paper presents an accurate approach to design a symmetrical linear antenna array (LAA) and a non‐uniformly excited single ring circular antenna array (CAA) to improve the far‐field radiation characteristics. The far‐field radiation pattern is improved with lower side lobe level (SLL) which is essential for the reduction of interference in the entire side lobe regions. A recently proposed meta‐heuristic based optimization algorithm called moth flame optimization (MFO) is applied to determine the optimal sets of current excitation weights and the inter‐element spacing among the array elements to reduce the SLL. In this context, 10‐element and 16‐element LAA and 8‐element, 10‐element, and 12‐element CAA design examples are presented by optimizing the array parameters. The simulation results obtained by using MFO algorithm based approach yield a considerable improvement in SLL and some marked improvement of half power beam width with respect to the uniform array pattern and those of the recently reported literature.